2018
DOI: 10.29252/hehp.6.2.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Education on the Knowledge, Attitude, and ‎Practice of Fast Food Consumption among Primary Students in ‎Tehran

Abstract: Assessment of fast food concumption ... [2] Determinants of fast food consumption among Iranian high school students based ... [3] Effects of fast food consumption on energy intake and diet quality among children in a national ... [4] Fast food consumption among US adults and children: Dietary and ... [5] The influence of market deregulation on fast food consumption and body mass index ... [6] Studing the extent of students' tendency towards fast foods and effective ... [7] Trends of fast food consumption amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Bandura’s self-regulatory learning principle emphasizes the active role of an individual in controlling, regulating, and managing oneself and the surrounding environment. 11 The constructs of this theory include: knowledge, outcome expectancy, outcome evaluation, situational understanding, self-efficacy, goal-setting or self-control, affective adaptation, and self-efficacy in overcoming barriers 12 (Figure 1). The main goal of social cognitive theory (SCT) is to explain human behavior in the form of triangular causality, which includes behavior, the environment, and personal factors (such as cognitions, emotions, and biological events).…”
Section: Introductionmentioning
confidence: 99%
“…Bandura’s self-regulatory learning principle emphasizes the active role of an individual in controlling, regulating, and managing oneself and the surrounding environment. 11 The constructs of this theory include: knowledge, outcome expectancy, outcome evaluation, situational understanding, self-efficacy, goal-setting or self-control, affective adaptation, and self-efficacy in overcoming barriers 12 (Figure 1). The main goal of social cognitive theory (SCT) is to explain human behavior in the form of triangular causality, which includes behavior, the environment, and personal factors (such as cognitions, emotions, and biological events).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge levels can be increased by implementing educational programs related to the side effects of junk food consumption. Shabanian et al (2018) found that an educational program was one of the efficient strategies to reduce the intake of fast food. That father's occupation is significantly associated with junk food consumption was supported by a study conducted in Nepal (Cohen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived severity depends on the individual's knowledge of the complications and risks of the disease and is rooted in the knowledge and awareness of the disease. Perceived sensitivity depends on a person's perception of the disease and its debilitative effects and is rooted in his or her attitudes (Safari, Shojaeizade, Ghofranipour, Heidarnia, & Amir, 2009). Accordingly, perceived sensitivity is experienced when people consider themselves susceptible to the severe complications of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%